(untitled) (Comunicação & Inovação, 2017)
This article examines social media as complementary tools to articulate people around community communication initiatives, Problematizing the use of these media in community activism and the building of a local political public sphere, our research, based on bibliographic research is divided in three parts: 1) community broadcasting resistance in times of convergence and social media as platforms of complementarity; 2) use of social media in community broadcasting initiatives; and 3) future challenges for developing a political public sphere around community broadcasting initiatives.